Game Monopoly Bahaya Narkoba Sebagai Media Edukasi Berbasis Android Di BNN Kota Dumai - Kirawan, Hari; Sellyana, Ari; Suhaidi, Mustahzzihim (Sekolah Tinggi Teknologi Dumai, 2024)
Communication between computer and android devices and networks can provide great benefits, especially in the delivery of information or learning. One of the media that can be used in the delivery of information or learning is a game or game. Information about the dangers of drugs presented by BNN Kota Dumai sometimes makes students less interesting and makes them less interested. BNN Kota Dumai is an institution tasked with preventing and eradicating narcotics abuse. BNN Kota Dumai in carrying out counseling on the dangers of drugs is still in the form of counseling activities. So that BNN Kota Dumai needs something interesting that can be used as a supporting tool in providing multimedia-based information. BNN Dumai City in conducting counseling on the dangers of drugs still uses PowerPoint which is still less effective and boring. It directly makes students less interested in participating in counseling on drug abuse in Dumai City, especially among high school students in Dumai City.